Atividade tocolítica in vitro do extrato etanólico e flavonoides isolados de Zornia brasiliensis Vogel (Leguminosae) em ratas - Ferreira, Sarah Rebeca Dantas (2018)
Once the ethanolic extract from the Z. brasiliensis aerial parts (ZB-EtOHAP) showed a spasmolytic effect in several smooth muscles, including ileum and trachea of guinea pig, rat aorta and cavernous body, and rat uterus, it was decided to characterize the mechanism of in vitro tocolytic action of ZB-EtOHAP in rats, in addition to evaluating and comparing a possible tocolytic effect of flavonoids isolated from this species. After euthanasia, the uterus was placed in baths for isolated organ where isotonic and isometric contractions were monitored (n = 5). Based on the fact that ZB-EtOHAP previously had a tocolytic effect in rat uterus on phasic contractions, it was decided to investigate its effect on oxytocin-induced tonic contractions (OXY) (EC50 = 5.5 ± 1.3 μg/mL). As the main smooth muscle relaxation pathways is the nitric oxide (NO), we decided to evaluate the participation of this pathway in tocolytic effect of ZB-EtOHAP. L-NAME, a non-selective NO synthase inhibitor (NOS), was used, and it was observed that the relaxing potency was decreased six-fold (EC50 = 35.6 ± 6.2 μg/mL) and partially reversed in the concomitant presence of L-NAME and L-arginine (10-3 e 3 x 10-3 M), substrate to NOS (EC50 = 24.8 ± 3.1 μg/mL; 45,4 ± 7,0 μg/mL, respectively), confirming the involvement NO pathway in the tocolytic effect of ZB-EtOHAP. Following the downstream pathway of intracellular NO signaling, the next step to be investigated was the participation of soluble guanylil cyclase (sCG) and protein kinase G (PKG). Therefore, it was observed that tocolytic potency of extract was reduced about 5 and 3 times in the presence of ODQ, an inhibitor of sCG (EC50 = 36.9 ± 7.3 μg/mL) and Rp-8-Br- PET-cGMPS, a PKG inhibitor (EC50 = 15.4 ± 2.7 μg/mL), respectively, confirming positive modulation of NO/sCG/PKG pathway in tocolytic effect of ZB-EtOHAP. As one of the targets of PKG are voltage-dependent calcium channels (CaV), it was proposed that the extract would be inhibiting these channels. It was observed that extract relaxed the pre-contracted uterus with KCl (EC50 = 22.0 ± 1.3 μg/mL), suggesting a participation of these channels. To confirm this hypothesis, cumulative curves to CaCl2 were performed in the absence and presence of ZB-EtOHAP, and a shift of control curves to the right was observed in the presence of extract with reduction of maximum effect. In addition, ZB-EtOHAP relaxed the pre-contracted uterus with S-(-)-Bay K8644, a CaV1 agonist, with about 4-fold lower potency (EC50 = 84.3 ± 10.6 μg/mL) in comparison to the effect observed with KCl, demonstrating that the extract indirectly inhibits the influx of Ca2+ through CaV1. As PKG can also modulate the K+ channels, we decided to investigate the effect of the extract in the presence of cesium chloride, a non-selective K+ channel blocker and a right shift of the extract control curve was observed (EC50 = 27.1 ± 3.0 μg/mL), confirming the participation of K+ channels in tocolytic effect of ZB-EtOHAP. To check which K+ channel subtype would be involved in this extract effect. selective blockers were used and it was observed that tocolytic potency was reduced in the presence of tetraethylammonium (EC50 = 16.8 ± 2.8 μg/mL), apamine (EC50 = 22.0 ± 3.3 μg/mL), glibenclamide (EC50 = 28.2 ± 5.3 μg/mL) and 4-aminopyridine (EC50 = 73.2 ± 13.4 μg/mL), potassium channel blockers: calciumactivated of large (BKCa) and small conductance (SKCa), ATP-sensitive (KATP) and voltagedependent (KV), respectively. No synergistic effect was observed when all of the abovementioned blockers were incubated simultaneously. It was also evaluated the tocolytic effect of two flavonoids isolated from ZB-EtOHPA, 7- methoxyflavone (7-MF) and 5,7dimethoxyflavone (5,7-DMF), and it was observed that both had a tocolytic effect, being 7-MF equipotent against OCY (IC50 = 3.2 ± 0.9 x 10-5 M) and CCh (IC50 = 4.3 ± 0.4 x 10-5 M) and 5,7DMF with potency about 2 times greater than CCh (IC50 = 1.7 ± 0.3 x 10-5 M) in relation to OCY (IC50 = 4.2 ± 1.0 x 10-5 M). Thus, action mechanism proposed for ZB-EtOHAP in rats may have positive modulation involvement in NO/sGC/PKG pathway and K+ channels, and Cav1 blockade and, consequently, Ca2+ influx decrease, promoting relaxation of smooth muscle uterine. In addition, the flavonoids, 7-MF and 5,7-DMF are probably responsible for tocolytic effect of extract.